GROWTH OF MSME IN UTTAR PRADESH AND INDIA: OUTLINING THE TRENDS IN GROWTH AND EMPLOYMENT GENERATION - Gupta, Akansha; Manju Rani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Micro, Small and Medium enterprises (MSME) hold a central position in India's economic advancement, supporting entrepreneurs, creating wealth, and promoting socio-economic development at the grassroots level. This study thoroughly explores the historical evolution and growth patterns of MSMEs in Uttar Pradesh and India. It meticulously analyses their growth and effect on employment generation using comprehensive secondary data from 1955 to 2016. By drawing information from diverse sources such as census records and economic surveys, it sheds light on how this sector has evolved and contributed to the workforce dynamics across different periods.